Increased ATPase activity promotes heat-resistance, high-yield, and high-quality traits in rice by improving energy status - Chen, Tingting; Ma, Jiaying; Xu, Chunmei; Jiang, Ning; Li, Guangyan; Fu, Weimeng; Feng, Baohua; Wang, Danying; Wu, Zhihai; Tao, Longxing; Fu, Guanfu (Frontiers in Plant Science, 2022)
Heat stress during the reproductive stage results in major losses in yield and quality, which might be mainly caused by an energy imbalance. However, how energy status affected heat response, yield and quality remains unclear. No relationships were observed among the heat resistance, yield, and quality of the forty-nine early rice cultivars under normal temperature conditions. However, two cultivars, Zhuliangyou30 (ZLY30) and Luliangyou35 (LLY35), differing in heat resistance, yield, and quality were detected. The yield was higher and the chalkiness degree was lower in ZLY30 than in LLY35. Decreases in yields and increases in the chalkiness degree with temperatures were more pronounced in LLY35 than in ZLY30. The accumulation and allocation (ratio of the panicle to the whole plant) of dry matter weight and non-structural carbohydrates were higher in ZLY30 than in LLY35 across all sowing times and temperatures. The accumulation and allocation of dry matter weight and non-structural carbohydrates in panicles were higher in ZLY30 than in LLY35. Similar patterns were observed in the relative expression levels of sucrose unloading related genes SUT1 and SUT2 in grains. The ATP content was higher in the grains of LLY35 than in ZLY30, whereas the ATPase activity, which determined the energy status, was significantly lower in the former than in the latter. Thus, increased ATPase activity, which improved the energy status of rice, was the factor mediating the balance among heat-resistance, high-yield, and high-quality traits in rice.